Health system governance in strengthening International Health Regulations (IHR) compliance in Myanmar. Issue 11 (2nd November 2020) - Pyone, Thidar; Aung, Toe Thiri; Endericks, Tina; Myint, Nyan Win; Inamdar, Leena; Collins, Samuel; Pwint, Khin Hnin; Hein, Bo Bo; Wilson, Anne
Abstract : The International Health Regulations 2005 (IHR) is a legally binding framework which requires 196 WHO Member States to take actions to prevent, protect against, control and provide public health response to the international spread of disease. Improving IHR compliance provides grounds for better health system strengthening, which is key to moving countries closer towards Universal Health Coverage. Multisectoral, collaborative working within and across sectors is fundamental to improving IHR (2005) compliance, and for that, governance is the best lever of the health system. This paper highlights the importance of the relationship between governance and IHR in the context of Sustainable Development Goals (SDGs) which follow the fundamental principle of interdependence; SDGs interlink with one another. We consider governance (SDG 16) and how it influences the IHR capacity of SDG 3 (health and well-being for all at all ages). This paper considers the successes of the Myanmar Ministry of Health and Sports thus far in improving IHR compliance and highlights that an even greater focus on health system governance would lead to more sustainable outcomes. Nurturing an institutional culture with enforced rules, which are conducive for improved accountability through inclusive participation would further improve Myanmar IHR strengthening efforts. Without those principles of good governance, the developed IHR capacities cannot be sustained or owned by Myanmar people. This has now become even more urgent given the current COVID-19 pandemic.